تحليل واقع التدقيق البيئي في الجزائر من منظور عينة من المدققين - زعيش ،محمد; خلايفية، ايمان (University of Eloued جامعة الوادي, 2025)
تهدف هذه الدراسة لمعرفة واقع التدقيق البيئي في الجزائر وهذا في ظل الاهتمام المتزايد بالبيئة على الصعيد الدولي والمحلي، حيث أصبح الافصاح عن المعلومات البيئية امر ضروري من قبل المؤسسات، ولتحقيق أهداف الدراسة تم الاعتماد على المنهج الوصفي التحليلي وللاجابة على إشكالية الدراسة واختبار فرضياتها تم توزيع إستبيان على عينة من المدققين الداخليين والخارجين في الجزائر. توصلت الدراسة لمجموعة من النتائج من أهمها أن أغلب المؤسسات الجزائرية تسعى للإستعانة بالتدقيق البيئي الذي يقدم رأي محايد حول الأداء البيئي للمؤسسة، وبالرغم من أهمية التدقيق البيئي إلا أنه هناك تأخر كبير في هذا المجال بالجزائر وهذا راجع لعدة أسباب لعل أهمها غياب تشريعات قانونية ومعايير تدقيق خاصة بالتدقيق البيئي. This study aims to understand the reality of environmental auditing in Algeria. This is in light of the growing interest in the environment at the international and local levels, where the disclosure of environmental information has become a necessity for institutions. To achieve the study's objectives, the descriptive analytical approach was adopted. To answer the study's problem and test its hypotheses, a questionnaire was distributed to a sample of internal and external auditors in Algeria . The study reached a number of results, the most important of which is that most Algerian institutions seek to utilize environmental auditing, which provides an impartial opinion on the institution's environmental performance. Despite the importance of environmental auditing, there is a significant delay in this field in Algeria. This is due to several reasons, perhaps the most important of which is the absence of legal legislation and auditing standards specific to environmental auditing.
Analysis of the reality of environmental auditing in Algeria from the perspective of a sample of auditors
مقال
Keywords: تدقيق; بيئي; افصاح; معايير; Audit; Environmental; Disclosure; Standards